Model‐based design and control of a small‐scale integrated continuous end‐to‐end mAb platform. (6th April 2020) - Gomis‐Fons, Joaquín; Schwarz, Hubert; Zhang, Liang; Andersson, Niklas; Nilsson, Bernt; Castan, Andreas; Solbrand, Anita; Stevenson, Joanne; Chotteau, Véronique
Abstract: A continuous integrated bioprocess available from the earliest stages of process development allows for an easier, more efficient and faster development and characterization of an integrated process as well as production of small‐scale drug candidates. The process presented in this article is a proof‐of‐concept of a continuous end‐to‐end monoclonal antibody production platform at a very small scale based on a 200 ml alternating tangential flow filtration perfusion bioreactor, integrated with the purification process with a model‐based design and control. The downstream process, consisting of a periodic twin‐column protein A capture, a virus inactivation, a CEX column and an AEX column, was compactly implemented in a single chromatography system, with a purification time of less than 4 hr. Monoclonal antibodies were produced for 17 days in a high cell density perfusion culture of CHO cells with titers up to 1.0 mg/ml. A digital twin of the downstream process was created by modelling all the chromatography steps. These models were used for real‐time decision making by the implementation of control strategies to automatize and optimize the operation of the process. A consistent glycosylation pattern of the purified product was ensured by the steady state operation of the process. Regarding the removal of impurities, at least a 4‐log reduction in the HCP levels was achieved. The recovery yield was up to 60%, and a maximum productivity of 0.8 mg/ml/day of purified product was obtained.